World insurance the evolution of a global risk network - Borscheid, Peter; Haueter, Niels Viggo (Oxford : Oxford University Press, 2012)
Traces the history and development of the international insurance and re-insurance business.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Insurance -- History